Outflow graft twisting of Heartmate III left ventricular-assisted device: A case report - Konukoğlu, Oğuz (Turk Gogus Kalp Damar Cerrahisi Derg, 2019)
Outflow graft twisting of Heartmate III left ventricular-assisted device is a rare device complication and, due to the recent reports from transplant centers, the firm and the United States Food and Drug Administration have announced explanatory measures. When the outflow graft twisting occurs, the diagnosis and treatment should be done without any delay due to serious decline in the device output and unstable hemodynamics. This article describes the first case of an outflow graft twisting in Turkey.